DO TRAINING, MOTIVATION, AND COMPENSATION INFLUENCE EMPLOYEE PERFORMANCE? (Case Study of Bireuen Regency BPBD Employees) - Faisal, Faisal; Syahriani, Endang (IndOmera, 2025)
The need for employee training is part of human resource development, motivating employees, and impacting their performance. Furthermore, compensation is expected to significantly contribute to employee performance. This research on employee performance within the Bireuen Regency Regional Disaster Management Agency (BPBD) attempted to investigate this issue. To this end, an associative method with a quantitative approach was applied, and a path analysis model was used. The analysis showed: (1) Employee performance is directly and indirectly related to the implementation of employee training, amounting to 26.6%. Work motivation contributes 32.3% and compensation implementation contributes 9.6%. (2) The analysis also demonstrated that all three factors—training, motivation, and compensation—simultaneously contribute significantly to employee performance, amounting to 38.2%.